Are the innovation processes in seaport terminal operations successful?. Issue 6 (18th August 2018) - Acciaro, Michele; Ferrari, Claudio; Lam, Jasmine SL; Macario, Rosario; Roumboutsos, Athena; Sys, Christa; Tei, Alessio; Vanelslander, Thierry
ABSTRACT: The maritime and port sector is widely considered conservative concerning the ability to introduce innovation in respect to other industries. This may be due to the lack of cooperative interactions among the several players involved. It does not mean that innovation does not occur in this industry. Along with some technical innovations, managerial, organizational, and cultural innovations also take place in the sector. The literature has considered the assessment and effects of the adoption of particular innovation, but still few studies underline the innovation path in a broad sense with a specific focus on terminal operators. The present article aims at filling this gap through a field analysis grouping together case studies developed in different world regions and examining the adoption path of innovation through a mix of three different techniques (i.e. the H- and I-indexes, a Systems of Innovation Analysis, and a Qualitative Comparative Analysis). Research outcomes underline how, even if no unique recipe for success can be found, specific factors (e.g. a ranking of innovation objectives, coordination among actors, and institutions) can influence the achievement of success. The analyses allow suggesting strategic and policy advice that may help link in a better way the innovation drivers with their actual effects.